3 - Choix stratégique de l'entreprise privée sénégalaise - DIA, Amadou Lamine (Africa Development, 1984)
In spite of specificities related to their small sizes, their individual or family base and environmental constraints , Senegalese businesses , just a big businesses can and must adopt a strategy. Many choices are available: specialization , diversification , regrouping , internationalization. Each of these can contribute to the financial balance , increase of outlets and growt of business. However , they all presuppose the availability of means which Senegalese businesses lack. Sub-contracting which consists in making a pro- duct by following guidelines set up by a supervisor who will later sell th product , turns out to be more suitable to the African context. Its short-comings are all in all less important than its advantages: possibility o diversification and modernization , increase of productivity and improve ment of the financial situation. Used adequately and with appropriat governmental measures , it is the best way of developing businesses , and i so doing , Senegal as a whole.